Craniovertebral fixation … a new technique of occipital – cervical fixation. (2nd December 2017) - Patkar, Sushil
Abstract: Background: Craniovertebral instability following transoral odontoid excision is usually treated by posterior occipital–cervical fixation using occipital plate and cervical lateral mass fixation with screw rod construct. A patient previously operated for basilar invagination had postoperative infection of both the transoral wound and the posterior implant site which needed removal of the posterior implant earlier. Clinical presentation: The patient presented with severe neck pain, myelopathy, and chronic discharging sinus in the posterior lower aspect the previous neck surgery wound. Reimaging revealed incomplete odontoid excision. He underwent repeat transoral odontoid excision. Treatment of the instability needed occipitocervical fixation avoiding, the atlas, axis (weakened by infection and previous implants), and the infected posterior cervical wound. A new technique using a customized plate rod construct, fixed anteriorly to the mid cervical vertebrae (by a standard mid cervical exposure) with the rods contoured to reach posteriorly through the safe paraspinal corridor and connected with domino connectors to occipital plate rods fixed on either side of midline by additional posterior exposure avoiding the midline scar was planned and executed successfully. Conclusion: This construct transfers the weight of the cranium to the cervical vertebral bodies along the physiological line of weight transmission and can be considered for distraction and reduction of basilar invagination with atlantoaxial dislocation. The technique seems to be safe and reproducible, but will need to tested over time with more cases.